2012
DOI: 10.1093/cvr/cvs239
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of fibronectin adhesion with contraction and relaxation in microvascular smooth muscle

Abstract: Changes in the receptor-mediated activation of the contractile apparatus cause parallel alterations in cell adhesion and cell cortical elasticity. These studies support the hypothesis that the regulation of cell adhesion is coordinated with contraction and demonstrate the dynamic nature of cell adhesion to the ECM. It is proposed that coordination of adhesion and VSMC contraction is an important mechanism that allows for an efficient transfer of force between the contractile apparatus of the cell and the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 43 publications
1
70
0
1
Order By: Relevance
“…Conversely, the VSMC stiffness level may be influencing the adhesion properties, as recently published work supports a mechanistic link between, stiffness and adhesion. Hong et al 43,44 demonstrated that treatment of VSMCs with the vasoactive agents angiotensin II or adenosine, respectively increase and decrease VSMC stiffness and adhesion in a coordinated manor. It may be that the interplay of these two mechanisms, VSMC stiffness and VSMC adhesion, contributes to the interaction of hypertension and aging in accelerating vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the VSMC stiffness level may be influencing the adhesion properties, as recently published work supports a mechanistic link between, stiffness and adhesion. Hong et al 43,44 demonstrated that treatment of VSMCs with the vasoactive agents angiotensin II or adenosine, respectively increase and decrease VSMC stiffness and adhesion in a coordinated manor. It may be that the interplay of these two mechanisms, VSMC stiffness and VSMC adhesion, contributes to the interaction of hypertension and aging in accelerating vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (AngII), a well characterized vasoconstrictor in the renin-angiotensin system, contributes to smooth muscle proliferation through increased integrin activation and enhanced application of mechanical forces to integrin adhesions [192, 193]. AngII induces smooth muscle adhesion to collagen and fibronectin through the AT1 receptor [192194], resulting in FAK-dependent ERK activation and enhanced cell proliferation [195, 196].…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…AngII induces smooth muscle adhesion to collagen and fibronectin through the AT1 receptor [192194], resulting in FAK-dependent ERK activation and enhanced cell proliferation [195, 196]. Cytoskeletal stiffening and contraction of smooth muscle cells treated with AngII results in elevated blood pressure [192, 193, 197], thereby enhancing mechanical load on the smooth muscle integrins. However, integrin signaling may also contribute to vasoconstriction, as treatment with the integrin inhibitor RGDS reduced vasoconstriction to AngII but not other vasoconstrictors [198].…”
Section: Integrins In Smooth Muscle Migration and Proliferationmentioning
confidence: 99%
“…AngII also strongly regulates vascular remodeling via VSMC hypertrophy and hyperplasia (70). In addition, AngII increases VSMC stiffness via increased VSMC E-modulus and adhesion to ECM proteins (59, 71). AngII-mediated vascular remodeling has been extensively studied and is mediated by a plethora of intracellular pathways downstream of the AngII type 1 receptor (AT 1 R); this triggers proproliferative, profibrotic, and pro-inflammatory signals, all contributing to progression of the disease.…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%